2011
DOI: 10.1179/174329409x409413
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of polypropylene by radiation grafting of hydrophilic monomers: Physicochemical properties

Abstract: 1 - ArticleThe surface of polypropylene was modified by the post-irradiation grafting of acrylic acid (AAc), N,N-dimethylacrylamide (DMA) and mixtures of AAc (DMA) and a quaternary ammonium salt (QAS). The polypropylene sheets were activated by electron beam radiation before the grafting reaction. The degree of grafting was determined by weighing and the surface hydrophilicity was measured by measuring the water contact angles. The presence of oxygen and nitrogen was demonstrated by XPS. The surface charge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…The melting peak became broader and the origin of another peak displaced toward a lower temperature was observed (153 1C). Similar behavior has been reported by several authors (Minkova et al, 1988;Kokostoski et al, 1990;Riquet et al, 2011). Changes to the peak for the irradiated PP sample may have been due to crystalline reorganization during irradiation with 100 kGy.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 73%
“…The melting peak became broader and the origin of another peak displaced toward a lower temperature was observed (153 1C). Similar behavior has been reported by several authors (Minkova et al, 1988;Kokostoski et al, 1990;Riquet et al, 2011). Changes to the peak for the irradiated PP sample may have been due to crystalline reorganization during irradiation with 100 kGy.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 73%
“…After exposing PP to a dose of 100 kGy, the melting peak became broader and the start of another peak was displaced to a lower temperature (153°C). Similar behavior has been reported by several authors (Kokostoski, Stojanovic, & Kacarevicpopovic, 1990;Riquet, Rohman, Guinault, & Demilly, 2011). Changes to the peak for the electron-beam PP sample may have been due to crystalline reorganization during the 100-kGy irradiation.…”
Section: Structural Variations Induced By Different Physical Treatmentssupporting
confidence: 72%
“…In another study, antimicrobial properties were imparted to PP film by pre-irradiation grafting of AA, N,N-dimethylacrylamide (DMA) and the mixtures of both AA and DMA with [2-methacryloyloxy)ethyl] trimethylammonium chloride using EB. The surface hydrophilicity varied depending on the monomer and comonomer grafted [ 181 ]. Adhesion tests for samples obtained from RIGC of N,N-dimethylacrylamide (DMA) and [2-methacryloyloxy)ethyl] trimethylammonium chloride (PMETAC) confirmed that adhesion depends mainly on the hydrophilicity and the roughness for the designed plastic surfaces for antimicrobial applications [ 179 ].…”
Section: Applications Of Grafted Polymers With Antimicrobial Propertiesmentioning
confidence: 99%